Adalimumab in Recalcitrant Severe Psoriasis Associated with Atopic Dermatitis - Savas Yayli (Case Reports in Dermatology, 2013)
Tumor necrosis factor-α inhibitors may induce various cutaneous side effects including eczematous-like lesions. The management of such side effects can be challenging. Herein, we report a case of a 55-year-old man who had a flare-up and subsequent improvement of atopic dermatitis during treatment of severe psoriasis with adalimumab.